2015
DOI: 10.1088/2040-8978/17/5/055901
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced absorption of thin-film photovoltaic cells using an optical cavity

Abstract: We show via numerical simulations that the absorption and solar energy conversion efficiency of a thin-film photovoltaic (PV) cell can be significantly enhanced by embedding it into an optical cavity. A reflective hemi-ellipsoid with an aperture for sunlight placed over a tilted PV cell reflects unabsorbed photons back to the cell, allowing for multiple opportunities for absorption. Ray tracing simulations predict that with the proposed cavity a textured thin-film silicon cell can exceed the Yablonovitch (Lamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…1(a), is chosen in this study to act as a 2D analog of inverted nanopyramids or nanocones, which was shown in previous studies to exhibit good light-trapping performance. [15][16][17][18][19][20][21][22][27][28] By using this grating design, it is possible to apply well-established grating theory to better understand the underlying mechanisms and find a design rule to govern light trapping.…”
Section: Principlementioning
confidence: 99%
See 1 more Smart Citation
“…1(a), is chosen in this study to act as a 2D analog of inverted nanopyramids or nanocones, which was shown in previous studies to exhibit good light-trapping performance. [15][16][17][18][19][20][21][22][27][28] By using this grating design, it is possible to apply well-established grating theory to better understand the underlying mechanisms and find a design rule to govern light trapping.…”
Section: Principlementioning
confidence: 99%
“…16,[18][19][20] Additionally, recent studies have shown that triangular, pyramidal, or conical gratings exhibit higher absorption due to the impedance match from air to silicon. [15][16][17][18][19][20][21][22]28,30,39 To improve light trapping even further, the inclusion of a back grating structure has been studied as a means to better scatter near-infrared light into guided resonances. [12][13][14]17,[27][28]33 By combining a front and back grating, recent studies have demonstrated enhancement to light trapping that outperforms absorbers that are textured only on one side.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is to be noted that the absorption peak is overbeating Yablonovitch limit near the band gap region in SPP waveguide configuration, which might be due to the strong light enhancement. It has been reported that the effective absorption in a thin-film solar cell can exceed the conventional limits with an efficient light trapping and enhancement structures [27,28] Since the proposed structure is periodic in X direction and infinitely long in the Y direction, plasmonic modes are not excited by a transverse electric (TE) polarized illumination.…”
Section: Resultsmentioning
confidence: 99%
“…Mode-coupling theory has been used to suggest that conventional limits can be surpassed in nano-photonic structures [20]. External cavities have also been proposed [21] in this context. Through experimental measurements guided by rigorous numerical solution of Maxwell's equations, Kuang et.…”
Section: 43%mentioning
confidence: 99%